ICU environment as a reservoir of KPC-ST307-Klebsiella pneumoniae high-risk clone resistant to ceftazidime-avibactam - Marta Hernández-García; Marta Nieto-Torres; Natalia Guerra-Pinto; Juan Antonio Castillo-Polo; Javier Saez de la Fuente; Malkoa Michelena; Manuel Ponce-Alonso; Cruz Soriano-Cuesta; Cristina Díaz-Agero; Rafael Cantón; Teresa M. Coque; Patricia Ruiz-Garbajosa (Scientific Reports)
Abstract We characterized all ceftazidime-avibactam-resistant KPC-producing K. pneumoniae (KPC-Kp) isolates recovered from both patients and environmental samples at the ICU of our hospital in 2020, during the COVID-19 pandemic initiation. Antimicrobial susceptibility testing (Sensititre-EUMDROXF; disk-diffusion) and WGS analysis (Illumina-Novaseq/Miseq; Oxford Nanopore®-MinION) were performed. Ten patients (16% of ICU patients) were colonized/infected by a ceftazidime-avibactam-resistant KPC-Kp isolate (March-December), six of them during/after treatment with ceftazidime-avibactam. Two ceftazidime-avibactam-resistant KPC-Kp were also recovered from two ICU sinks (July-September). All isolates belonged to ST307 clone and had identical resistance gene content. Six KPC-variants were detected in patient isolates (KPC-62, KPC-92, KPC-150, KPC-66, KPC-53, KPC-46). KPC-92 and KPC-66 variants were also detected in sink isolates. Regardless of the origin (patients or sinks), KPC-92-, KPC-150 and KPC-62-Kp isolates combining altered porin proteins also exhibited increased/resistant MIC values to cefiderocol, cefepime-taniborbactam, aztreonam-avibactam, meropenem-vaborbactam and/or imipenem-relebactam. A cgMLST analysis demonstrated the clonal spread of KPC-ST307-Kp within the ICU, between patients and the hospital environment. Clustering was observed mainly by KPC variants (KPC-92, KPC-62). A variant calling analysis and plasmid characterization showed possible transmission between patients and sinks. Our results suggest that the patient care environment likely contributed to persistence and spread of last-line antibiotics-resistant KPC-Kp within the ICU during the COVID-19 pandemic.